Pathogen safety of a pasteurized four‐factor human prothrombin complex concentrate preparation using serial 20N virus filtration. Issue 5 (12th February 2017) - Nowak, Thomas; Popp, Birgit; Gröner, Albrecht; Schäfer, Wolfram; Kalina, Uwe; Enssle, Karlheinz; Roth, Nathan J.
Abstract : BACKGROUND: Beriplex P/N/Kcentra/Coaplex/Confidex is a four‐factor human prothrombin complex concentrate (PCC). Here, we describe the pathogen safety profile and biochemical characteristics of an improved manufacturing process that further enhances the virus safety of Beriplex P/N. STUDY DESIGN AND METHODS: Samples of product intermediates were spiked with test viruses, and prions were evaluated under routine production and robustness conditions of the scale‐down version of the commercial manufacturing process for their capacity to inactivate or remove pathogens. The PCC was characterized by determining the activity of Factor (F)II, FVII, FIX, FX, protein C, and protein S and the concentration of heparin and antithrombin III in nine product lots. RESULTS: The manufacturing process had a very high virus reduction capacity for a broad variety of virus challenges (overall reduction factors ≥15.5 to ≥18.4 log for enveloped viruses and 11.5 to ≥11.9 log for nonenveloped viruses). The high virus clearance capacity was provided by two dedicated virus reduction steps (pasteurization and serial 20N virus filtration) that provided effective inactivation and removal of viruses and a purification step (ammonium sulfate precipitation and adsorption to calcium phosphate) that contributed to the overall virus removal capacity. The diethylaminoethyl (DEAE) chromatography and ammonium sulfate precipitation steps removed prions to below the limit of detection. The levels of different clotting factors in the final product were well balanced. CONCLUSION: The improved manufacturing process of Beriplex P/N further enhances the margin of pathogen safety based on its capacity to remove and inactivate a wide range of virus challenges.